Venn-diagram strategy in EFL class to enhance learners’ writing skill and motivation - Muhammad Lukman Syafii; M. Zaini Miftah (Journal on English as a Foreign Language, 2020)
This classroom action research was intended to enhance students' skills and motivation in writing report texts by implementing the Venn-diagram strategy. Twenty-one students failing to achieve the passing grade level of scores on their writing skills at the ninth grade of an Islamic secondary school in East Java Indonesia became the subjects of the study. The observation checklist, field notes, questionnaires, and writing test were used to collect data through implementing the Venn-diagram strategy taking a two-set circle and applying the writing process – prewriting via generating ideas, selecting relevant ideas, and ordering ideas; drafting general classification and description paragraphs; revising the rough draft and editing it; and publishing a final version. The results showed that the strategy can enhance the learners’ skills and their motivation in writing report text. The learners’ writing scores significantly increased both in two cycles – thirteen learners of the twenty-one students passed from the passing grade level in Cycle 1, and all learners passed from those in Cycle 2. It also highly motivates learners in writing report text, both in two cycles. Therefore, English teachers are recommended to apply Venn-diagram strategy in EFL writing class to start writing.